(4-Oxo-2-thioxothiazolidin-3-yl)acetic acids as potent and selective aldose reductase inhibitors. (1st December 2020) - Kucerova-Chlupacova, Marta; Halakova, Dominika; Majekova, Magdalena; Treml, Jakub; Stefek, Milan; Soltesova Prnova, Marta
Abstract: (4-Oxo-2-thioxothiazolidin-3-yl)acetic acids exhibit a wide range of pharmacological activities. Among them, the only derivative used in clinical practice is the aldose reductase inhibitor epalrestat. Structurally related compounds, [(5 Z )-(5-arylalkylidene-4-oxo-2-thioxo-1, 3-thiazolidin-3-yl)]acetic acid derivatives were prepared previously as potential antifungal agents. This study was aimed at the determination of aldose reductase inhibitory action of the compounds in comparison with epalrestat and evaluation of structure-activity relationships (SAR). The aldose reductase (ALR2) enzyme was isolated from the rat eye lenses, while aldehyde reductase (ALR1) was obtained from the kidneys. The compounds studied were found to be potent inhibitors of ALR2 with submicromolar IC50 values. ( Z )-2-(5-(1-(5-butylpyrazin-2-yl)ethylidene)-4-oxo-2-thioxothiazolidin-3-yl)acetic acid (3 ) was identified as the most efficacious inhibitor (over five times more potent than epalrestat) with mixed-type inhibition. All the compounds also exhibited low antiproliferative (cytotoxic) activity to the HepG2 cell line. Molecular docking simulations of 3 into the binding site of the aldose reductase enzyme identified His110, Trp111, Tyr48, and Leu300 as the crucial interaction counterparts responsible for the high-affinity binding. The selectivity factor for 3 in relation to the structurally related ALR1 was comparable to that for epalrestat. SAR conclusions suggest possible modifications to improve further inhibition efficacy, selectivity, and biological availability in the group of rhodanine carboxylic acids. Graphical abstract: Image 1 Highlights: Six rhodanine acetic acid derivatives were tested for aldose reductase inhibition. Four compounds inhibited aldose reductase more potently than epalrestat. Inhibition selectivity relative to aldehyde reductase exceeded that of epalrestat. Negligible cytotoxicity to the HepG2 cell line was recorded for all compounds. SAR evaluation indicated a way how to improve inhibition parameters further.